Study of urban infrastructure elements for personal mobility devices safe movement - V. V. Donchenko; V. A. Kupavtsev (Вестник СибАДИ, 2023)
Introduction. Despite the introduction of new amendments to the rules of the road, accidents involving personal mobility device (PMD) continue to occur on the roads of the Russian Federation. The analysis of statistical indicators makes possible to determine that more than 90% of accidents occur in populated areas, with the participation of PMDs equipped with electric motor mainly collisions with vehicles, with less powerful, not equipped with electric motor mainly collisions with pedestrians occur, which indicates certain chosen conditions for driving - the roadway and sidewalks. In addition, it was found that in these cases, one of the emerging types of accidents is tipping, associated primarily with the available elements on sections of city streets and city roads, which have a certain height above the level of roads and sidewalks. In order to determine the possibility of a overturning taking these elements into account, the analysis of the urban infrastructure was determined, the main elements that pose a risk to PMD traffic were identified, their geometric parameters were established and a mathematical calculation of the traffic conditions was carried out in the study. Methods and materials. As materials and methods for the study, the methods of statistical analysis and mathematical calculations were defined. Results. As a result of the calculation, the authors identified the elements of the urban infrastructure that are dangerous for the movement of the PMD, when interacting with which, with a high degree of probability, the device in question will overturn and injure the driver of the PMD. Conclusion. The calculations have identified the main hazardous elements located on the city streets and urban roads. It was found that the process of overturning is influenced by the geometric characteristics of the device. In view of the obtained results, the perspective directions of improvement of traffic safety in urban transport systems - development of requirements for safety PMD and creation of specialized infrastructure for the safe movement of the PMD in the conditions of modern cities were determined.